Has the development of the digital economy improved green total factor productivity in China?—A study based on data at the provincial level in China - Wang, Shijin; Xue, Zhichao (Frontiers in Environmental Science, 2023)
China's economic development has entered a new historical stage, and it is crucial to coordinate the linkage between economic development, resource allocation and environmental protection in this new stage. In view of this, this paper selects the panel data of 30 provinces (municipalities and autonomous regions) in China from 2011 to 2020, and firstly measures the Green Total Factor Productivity (GTFP) by using Slack Based Measure -Malmquist Luenberger method (SBM-ML); Then, the relationship between the development of digital economy and regional GTFP is analyzed by using the two-way fixed effect model and threshold effect; Finally, relevant policy suggestions are put forward. This paper found that: firstly, the development of digital economy significantly improves China's GTFP, and the conclusion still valid after considering a series of robustness tests; Secondly, there are obvious disparities in the development level of digital economy among provinces, and the development level of coastal areas is generally higher than that of inland areas, and according to the sub-regional regression results, the positive effect of digital economy on GTFP has regional heterogeneity, and the development of digital economy in coastal areas has a more significant effect on the enhancement of GTFP, while this effect in inland areas does not pass the significance test; Thirdly, according to the threshold effect test results, there is also a single threshold effect with institutional environment and technological innovation as the threshold variables for the impact of digital economy on GTFP in China.